1988
DOI: 10.1111/j.1532-5415.1988.tb04397.x
|View full text |Cite
|
Sign up to set email alerts
|

What are the Psychiatric Manifestations of Vitamin B12 Deficiency?

Abstract: Psychiatric symptoms attributable to vitamin B12 deficiency have been described for decades. The earlier reports are for the most part in accord with more recent ones, despite being diagnostically less specific in psychiatric and hematologic terms. These symptoms seem to fall into several clinically separate categories: slow cerebration; confusion; memory changes; delirium, with or without hallucinations and/or delusions; depression; acute psychotic states; and (more rarely) reversible manic and schizophrenifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(72 citation statements)
references
References 73 publications
2
66
1
2
Order By: Relevance
“…When patients with dementia syndromes are investi gated, serum Bi2 is routinely analyzed to identify vita min B12 deficiency, which is considered to be a poten tially treatable form of secondary dementia [32], al though its reversibility has been questioned [33].…”
Section: Resultsmentioning
confidence: 99%
“…When patients with dementia syndromes are investi gated, serum Bi2 is routinely analyzed to identify vita min B12 deficiency, which is considered to be a poten tially treatable form of secondary dementia [32], al though its reversibility has been questioned [33].…”
Section: Resultsmentioning
confidence: 99%
“…With vitamin deficiency, psychological symptoms such as depression and hysteria may appear [155]. Deficiency of vitamin B12 and folate are associated with psychiatric symptoms, including dementia and depression [156]. Iron deficiency, which is not uncommon in third world countries, has occasionally been associated with symptoms of depression, and if anemia is present, poor mood, lethargy, and difficulties sustaining attention [157].…”
Section: Hedonic and Mood-related Effects Of Sodium Deficiencymentioning
confidence: 99%
“…Numerous investigators have reported associations between deficiencies of folate or vitamin B 12 and psychiatric syndromes including depression and dementia [32][33][34][35][36][37][38] . Some workers have hypothesized that in the elderly cognitive impairment and organic psychosis are often associated with B 12 deficiency 36 , whereas depression is associated with folate deficiency 34,38 . However, it should be remembered that in a sample of geriatric patients only 3.7% were B 12 and 1.3% folate deficient 39 .…”
Section: Micro-nutrient Status and Moodmentioning
confidence: 99%